Entrepreneurship Education and Entrepreneurial Intention: Perspectives on Institutional Theory - Wannamakok, Wisuwat; Liang, Wen-ke (Journal of Entrepreneurship, Business and Economics; Vol 7 No 2 (2019), 2019)
Entrepreneurial intentions have been considered a critical element understanding the formation of new venture creations that have been seen in creating jobs and economic growth in a country. This study draws upon institutional environment theory to clarify and test the model using multiple linear regression on entrepreneurship education and three determinants of institutional environment dimensions, namely, regulatory, cogni-tive, and normative dimensions toward entrepreneurial intentions in the context of Esto-nia. A questionnaire-based survey on 265 Estonian university students was conducted to validate the hypotheses of the study. The results suggest that entrepreneurship education has a significant influence on university students’ entrepreneurial intention. Additionally, all three institutional environment determinants moderate the positive relationship be-tween entrepreneurship education and entrepreneurial intention. Interestingly, interaction terms among normative environment, entrepreneurship education, and entrepreneurial intention are statistically significant. Therefore, the results of this study advance institu-tional theory and its application in entrepreneurship research in the context of Estonia. Research paper Keywords: Entrepreneurship education, Entrepreneurial intentions, Institutional environment theory, Estonia, University students Reference to this paper should be made as follows: Wannamakok, W., & Liang, W. (2019). Entrepreneurship Education and Entrepreneurial Intention: Perspectives on Institutional Theory, Journal of Entrepreneurship, Business and Economics , 7 (2), 106–129.